Sulforaphane Impacts Invasion Capacity and Proliferation of Triple Negative Breast Cancer Cells Grown in the Presence of Tumor-associated Macrophages (P05-003-19) - Jensen, Katherine (Curr Dev Nutr, 2019)
OBJECTIVES: Triple negative breast cancer (TNBC) accounts for 12% to 24% of all breast cancer cases and is characterized by higher proliferation rates and an increased likelihood of tissue invasion. Tumor cells and cells in the tumor microenvironment (TME), specifically tumor associated macrophages (TAMs), interact through signaling (e.g., cytokines) to promote cancer progression by increasing proliferation and invasion capacity. Sulforaphane (SFN) is an isothiocyanate derived from cruciferous vegetables (i.e., broccoli) that has shown promising results in hindering TNBC progression. SFN reduced proliferation in breast cancer cells and altered cytokine signaling between breast cancer cells and cells in the TME (adipocytes). SFN also decreased invasion markers in TNBC cells grown in isolation. However, TAMs promote tumor cell aggression, and SFN's effect in multicellular environments is unclear. To determine SFN's potential in cancer treatment, it is critical to investigate SFN's effect on proliferation and invasion capacity of TNBC cells grown under TAMs influence, not just grown in isolation. The objective of this study was to determine if SFN can reduce proliferation and invasion capacity of TNBC cells grown in TAM secretions. METHODS: For cell proliferation, TNBC cells (MDA-MB-231) were exposed to TAM secretions using conditioned media and were then treated with SFN (10 μM) or DMSO vehicle control for 24 and 48 hours. Proliferation was measured using a MTT-based assay and cell counts. For invasion, TAMS and TNBC cells were co-cultured for 48 hours in transwell plates. Prior to co-culture period, cells were treated with SFN (15 μM) or vehicle control. Invasion capacity was measured through a transwell invasion assay with collagen representing the tumor basement membrane. ANOVA and t-tests were used to determine statistical differences with significance at P = 0.05. RESULTS: Preliminary analysis revealed significant reductions in proliferation for TAM exposed TNBC cells after 24 hours (P = 0. 0132) and 48 hours (P = 0. 0190) of SFN treatment. CONCLUSIONS: SFN reduced proliferation and can potentially reduce invasion capacity of TNBC cells influenced by TAM secretions thus enhancing future utilization of SFN in TNBC treatment regimens. FUNDING SOURCES: California State University, Chico.